Knowledge, Attitude and Practices Regarding Hepatitis C Prevention among People of Rural Community, Lahore - Nawaz, Kiran; Hussain, M.; Majeed, Iram; Afzal, M.; Gilani, Syed Amir (International Journal of Social Sciences and Management, 2018)
Introduction: Hepatitis C infection is developing risk and real burden on general wellbeing, overall prevalence of hepatitis C is 3% (170 million tainted individuals). Roughly 10 million individuals are contaminated in Pakistan and prevalence is relied upon to be higher in isolated places. Methodology: This was descriptive cross-sectional study. Convenient sampling was used and data was analyzed by SPSS version 21. Results: The findings of the research were good Response rate of this review was 100 % and mean number of "Yes" answers to knowledge, behavior and practice questions were 51%, 46% and 42% individually. Conclusions: Knowledge, attitude and practice about hepatitis C among adolescences was insignificant. Consequences of this investigation show lack of understanding about disease control and prevention. The level of knowledge was good among people but there was no significant association between attitude and practices. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 138-145